7(1-3b)-2b=-2(5+3b)

Simple and best practice solution for 7(1-3b)-2b=-2(5+3b) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(1-3b)-2b=-2(5+3b) equation:


Simplifying
7(1 + -3b) + -2b = -2(5 + 3b)
(1 * 7 + -3b * 7) + -2b = -2(5 + 3b)
(7 + -21b) + -2b = -2(5 + 3b)

Combine like terms: -21b + -2b = -23b
7 + -23b = -2(5 + 3b)
7 + -23b = (5 * -2 + 3b * -2)
7 + -23b = (-10 + -6b)

Solving
7 + -23b = -10 + -6b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '6b' to each side of the equation.
7 + -23b + 6b = -10 + -6b + 6b

Combine like terms: -23b + 6b = -17b
7 + -17b = -10 + -6b + 6b

Combine like terms: -6b + 6b = 0
7 + -17b = -10 + 0
7 + -17b = -10

Add '-7' to each side of the equation.
7 + -7 + -17b = -10 + -7

Combine like terms: 7 + -7 = 0
0 + -17b = -10 + -7
-17b = -10 + -7

Combine like terms: -10 + -7 = -17
-17b = -17

Divide each side by '-17'.
b = 1

Simplifying
b = 1

See similar equations:

| 5X+8y=0 | | -6=(1/5)y-1 | | ln(x-1)+ln(x+4)=ln(2x+2) | | -5x-2(x-4)=-4x-4(2x-2) | | -15=5-5x | | -4(x+16)=6(x+6) | | m-14=18+5m | | -7x-6x=-3(2x+5)-3(x-5) | | -9x-4=-2x-6x-2 | | 0=8+8 | | 2z^2+2z+5=0 | | -5=3m-3 | | (1/5)(x-8)=x-16 | | x^2-4xy+4y^2=0 | | x^6=8 | | (6y+2y+1)+(2y+3)-(5y-2Y)= | | e^6=7 | | 9x-6=x-22 | | (p+20)+p+(2p-32)=400 | | 16-3p+2p=3p-4 | | 5-4x=13-8x | | 1-6m=-1-6m+2+m | | (3x)(3x)-12(3x)+27=0 | | 7x-6=-10+8x | | (1/4)(z+2)=(3/4) | | 192-7x=29x+20 | | 7x-6=10+8x | | (p+20)+p+(4p-32)=400 | | 3y^2-10y-11=0 | | -3x^2-49=0 | | 1-6m=1-6m+2+m | | 12-3x=8-x |

Equations solver categories